A two-dimensional lanthanide metal-organic framework material and its preparation method and application
By using two-dimensional lanthanide metal-organic framework materials as fluorescent probes, the problem of insufficient sensitivity to TNP detection by existing detection methods is solved, and the detection effect of high sensitivity, simple operation and fast reaction is achieved.
Patent Information
- Application Number
- CN202411659738.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing detection methods have problems such as insufficient sensitivity, complex operation and long reaction time for detecting nitro aromatic explosives (such as TNP), and it is difficult to meet the needs of fast, simple and efficient detection.
The two-dimensional lanthanide metal-organic framework material is used as the fluorescence probe to synthesize the material through solvothermal reaction, and fluorescence detection is performed using its characteristic emission peaks to achieve selectivity, sensitivity and cyclic detection of TNP.
It realizes high sensitivity detection for TNP, has the advantages of simple operation, fast reaction time and strong anti-interference ability, and provides an environmentally friendly and efficient trace detection method.
Smart Images

Figure CN119264456B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of detection material preparation, and specifically relates to a two-dimensional lanthanide metal-organic framework material and a preparation method and application thereof. Background Art
[0002] Metal-organic frameworks (MOFs) are a class of hybrid materials formed by metal ions and organic ligands connected by coordination. The large specific surface area, designable structure and high porosity of MOF have made it widely used in gas storage / separation, catalysis, molecular recognition, proton conduction and luminescent sensing. Lanthanide elements have unique properties, such as 4f intra-transition or 4f-5d transition, atomic magnetic moment and strong spin coupling, making them excellent candidates for constructing lanthanide MOF (Ln-MOF). Ln-MOF combines the advantages of MOF and lanthanide ions, with diverse crystal structures, strong photoluminescence, unique sharp line emission from visible to infrared regions, long fluorescence lifetime and large Stokes shift. The characteristic luminescence of Ln-MOF can be attributed to the energy transfer between metal and ligand, also known as the "antenna effect". On the one hand, this effect will make Ln 3+ The efficient luminescence is generated, but it also depends on the coordination position of the singlet and triplet states of the relevant elements in the coordination compound. On the other hand, the trivalent lanthanide metal cations, such as Eu 3+ and Tb 3+ Due to its high color purity, fluorescence efficiency and sensitivity to the coordination environment, its research has received extensive attention. 3+ Combining them to construct LnMOF is a novel and practical synthetic strategy.
[0003] So far, researchers have successfully applied LnMOFs to many fields, such as sensing, light-emitting devices, proton conduction, bioimaging, etc. However, among various applications, fluorescence detection based on chemical sensing is the best choice for rapid identification and detection of ions, small molecules and vapors. Compared with traditional detection methods, fluorescence detection has many advantages such as high sensitivity, convenience, rapid response and practicality. Nitroaromatic compounds (NACs) are a class of highly toxic and explosive substances that are extremely harmful to the environment and humans. Generally speaking, explosives are detected using police dogs or high-precision instruments, which usually requires a lot of manpower and material resources. At present, fluorescence detection of explosives based on chemical sensing has attracted more and more attention because this detection method has the advantages of high sensitivity, simple operation, fast response time and can be applied in both solid and liquid states. Explosives mainly include the following: 1,3-DNB, 2,4-DNT, TNT, TNP and DMNB, etc. They are all electron-deficient nitrogen compounds and typical electron acceptors. Therefore, when they are close to electron-rich electron donors, the electron-rich electron donors will be quenched due to the presence of photoinduced electron transfer, thus changing the fluorescence spectrum. In particular, TNP is widely used in dyes, leather, fireworks and other industries. Improper handling will endanger human health, and it is urgent to develop convenient and economical detection methods. Summary of the invention
[0004] In response to the above problems, the present invention proposes a two-dimensional lanthanide metal-organic framework material and a preparation method and application thereof, and detects TNP by using the two-dimensional lanthanide metal-organic framework as a fluorescent probe, with the aim of obtaining a new method for detecting TNP with high sensitivity, simple operation and fast reaction time.
[0005] A method for preparing a two-dimensional lanthanide metal-organic framework material comprises the following steps:
[0006] S1: Europium nitrate hexahydrate (Eu(NO 3 ) 3 6H 2 O) and organic ligands (H 2 dptz) is dissolved in a mixture of hydrochloric acid, acetonitrile and water to obtain a mixture;
[0007] S2: The mixture is sealed in a stainless steel autoclave lined with tetrafluoroethylene for heating, cooled to room temperature after heating, and then repeatedly washed with acetonitrile for 3-5 times to separate and obtain colorless block crystals;
[0008] S3: drying the colorless bulk crystals to obtain a two-dimensional lanthanide metal-organic framework material;
[0009] The organic ligand (H 2 The chemical formula of dptz is: C 15 H 10 N 4 O 4 , where the molecular formula of dptz is C 15 H 8 N 4 O 4 ;
[0010] The organic ligand (H 2 dptz) structure is as follows:
[0011] ;
[0012] The europium nitrate hexahydrate and the organic ligand (H 2 dptz) mass ratio 1.5-2:1;
[0013] The amount of hydrochloric acid and organic ligand in step S1 is in the following relationship: 45-50 mL: 1 g;
[0014] The volume ratio of hydrochloric acid, acetonitrile and water in step S1 is 1:9.5-10:1.5-2;
[0015] The concentration of hydrochloric acid in step S1 is 0.8-1 mol·L -1 ;
[0016] The heating in step S2 is specifically: heating to 160-170°C at a rate of 10-15°C / h, and then keeping the temperature for 72-78h; the cooling is cooling at a rate of 5-8°C / h;
[0017] The drying in step S3 is performed at room temperature;
[0018] The two-dimensional lanthanide metal-organic framework material in step S3 has the general formula [Eu(dptz)(H 2 O) 2 ]Cl·3H 2 Oh,
[0019] Belongs to the monoclinic system, space group is P2 1 / n, the unit cell parameters are a(Å)=10.7002(13), b(Å)=14.067(2), c(Å)=12.7584(16), α(°)=90, β(°)=96.207(4), γ(°)=90, and the volume V(Å 3 )=1909.1(4).
[0020] A two-dimensional lanthanide metal-organic framework material prepared by the above preparation method;
[0021] An application of the above two-dimensional lanthanide metal-organic framework material as a fluorescent probe to detect TNP.
[0022] The beneficial effects of the present invention are:
[0023] Under solvothermal reaction conditions, a two-dimensional lanthanide metal-organic framework was rationally designed and synthesized. The crystal exhibited the characteristic emission peak of europium ions and had fluorescence spectra of different intensities when used as a fluorescent probe in the detection process of different nitroaromatic explosives. The crystal can selectively, sensitively and cyclically detect TNP through fluorescence quenching, and exhibited excellent anti-interference ability during the detection process. Therefore, the crystal is an environmentally friendly and efficient sensor for trace detection of TNP. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the crystal coordination structure of the two-dimensional lanthanide metal-organic framework material of the present invention;
[0025] Figure 2 A ball-and-stick schematic diagram of a binuclear europium cluster in a two-dimensional lanthanide metal-organic framework material crystal of the present invention;
[0026] Figure 3 The spatial packing diagram of the two-dimensional lanthanide metal-organic framework material crystals of the present invention;
[0027] Figure 4 The ball-and-stick stacking diagram of the two-dimensional layered structure of the two-dimensional lanthanide metal-organic framework material crystal of the present invention;
[0028] Figure 5 Coordination environment diagram of organic ligands in the two-dimensional lanthanide metal-organic framework material crystal of the present invention;
[0029] Figure 6 Coordination environment diagram of binuclear europium clusters in the two-dimensional lanthanide metal-organic framework material crystal of the present invention;
[0030] Figure 7 The layered (3,6) topology of the two-dimensional lanthanide metal-organic framework material crystal of the present invention;
[0031] Figure 8 PXRD comparison diagram of the two-dimensional lanthanide metal-organic framework material synthesized by the present invention and the simulated sample;
[0032] Fig. 9 PXRD comparison diagram of the two-dimensional lanthanide metal-organic framework material synthesized by the present invention and the simulated sample after being immersed in water for three days and five days;
[0033] Fig.10PXRD comparison diagram of the two-dimensional lanthanide metal-organic framework material synthesized by the present invention after being immersed in aqueous solutions of different pH values and the simulated samples;
[0034] Fig.11 Thermogravimetric curve of the two-dimensional lanthanide metal-organic framework material crystal of the present invention;
[0035] Fig.12 The emission spectrum of the organic ligand used in the present invention in the solid state;
[0036] Fig.13 Excitation and emission spectra of the two-dimensional lanthanide metal-organic framework material crystals of the present invention in the solid state;
[0037] Fig.14 The emission spectra of the two-dimensional lanthanide metal-organic framework material crystals of the present invention in aqueous solutions containing different nitroaromatic explosives;
[0038] Fig.15 The emission spectra of the two-dimensional lanthanide metal-organic framework material crystals of the present invention in aqueous solutions containing different concentrations of TNP;
[0039] Fig.16 Stern-Volmer plot of the two-dimensional lanthanide metal-organic framework material crystal to TNP of the present invention;
[0040] Fig.17 The anti-interference study of the two-dimensional lanthanide metal-organic framework material crystal to TNP in the presence of different nitroaromatic explosives;
[0041] Fig.18 The present invention is a two-dimensional lanthanide metal-organic framework material crystal that can be recycled after TNP detection. DETAILED DESCRIPTION
[0042] The organic ligand (H 2 dptz) is a commercially available product with a purity of more than 98%.
[0043] Organic ligand (H 2 The chemical formula of dptz is: C 15 H 10 N 4 O 4 , the English name is: 3-(3,5-dicarboxylphenyl)-5-(pyrid-2-yl)-1H-1,2,4-triazole, where the molecular formula of dptz is C 15 H 8 N 4 O 4 .
[0044] Example 1
[0045] 0.02 g of Eu(NO 3 ) 3 6H 2 O and 0.01 g H 2 dptz was dissolved in 0.5 mL of hydrochloric acid (1 mol·L -1 ), 5 mL of acetonitrile and 1 mL of water to obtain a mixture; the mixture is sealed in a stainless steel autoclave lined with tetrafluoroethylene, and then the stainless steel autoclave is placed in an oven and heated to 160°C at a rate of 10°C / h, and then kept warm for 72 hours, and then cooled to room temperature at a rate of 5°C / h, and finally washed repeatedly with acetonitrile to separate colorless block crystals, and the crystals are dried in a room to obtain the two-dimensional lanthanide metal-organic framework material with a yield of 70%;
[0046] Example 2
[0047] 0.02 g of Eu(NO 3 ) 3 6H 2 O and 0.01 g H 2 dptz was dissolved in 0.5 mL of hydrochloric acid (0.8 mol·L -1 ), 5 mL of acetonitrile and 1 mL of water to obtain a mixture; the mixture is sealed in a stainless steel autoclave lined with tetrafluoroethylene, and then the stainless steel autoclave is placed in an oven and heated to 170°C at a rate of 10°C / h, and then kept warm for 78 hours, and then cooled to room temperature at a rate of 8°C / h, and finally washed repeatedly with acetonitrile to separate colorless block crystals, and the crystals are dried in a room to obtain the two-dimensional lanthanide metal-organic framework material with a yield of 71.8%;
[0048] Example 3
[0049] 0.03 g of Eu(NO 3 ) 3 6H 2 O and 0.02 g H 2 dptz was dissolved in 0.9 mL of hydrochloric acid (1 mol·L -1 ), 9 mL of acetonitrile and 1.8 mL of water to obtain a mixture; the mixture was sealed in a stainless steel autoclave lined with tetrafluoroethylene, and the stainless steel autoclave was then placed in an oven and heated to 170°C at a rate of 15°C / h, then kept warm for 72 h, and then cooled to room temperature at a rate of 8°C / h, and finally washed repeatedly with acetonitrile to separate colorless block crystals, and the crystals were dried in a room to obtain the two-dimensional lanthanide metal-organic framework material with a yield of 72.5%.
[0050] Comparative Example 1
[0051] The amount of acetonitrile in Example 3 was adjusted to 2 mL, and other processes and reaction conditions were not changed. Finally, no two-dimensional lanthanide metal-organic framework crystals were obtained. After reducing the amount of acetonitrile solvent, Eu(NO 3 ) 3 6H 2 O and H 2 The two monomers of dptz were not fully dissolved, resulting in the inability to successfully synthesize crystals in the later stage.
[0052] Comparative Example 2
[0053] The heating temperature in Example 3 was changed to 120°C, and other processes and reaction conditions remained unchanged. In the end, no two-dimensional lanthanide metal-organic framework crystals were obtained. This is mainly because chemical reactions require a certain temperature to obtain energy and overcome the energy barrier of the reaction; when the temperature is too low, the reactants cannot obtain enough energy, resulting in the reaction being unable to proceed or proceeding very slowly, and thus unable to form crystals; moreover, the properties of the solvent (such as polarity and coordination ability) will change at different temperatures. When the temperature is too low, the physicochemical properties of the solvent are not conducive to the dissolution and coordination of the reactants, thereby affecting the formation of crystals; changes in temperature will affect the solubility of the reactants. If the temperature is too low, the solubility of the reactants will decrease, resulting in the inability of the reactants to fully dissolve, thereby affecting the synthesis of the crystals. For europium ions with flexible coordination modes and organic ligands H with multiple coordination sites, 2 dptz, changes in temperature will affect its coordination mode. Too low a temperature will cause the coordination mode to be unstable, thus failing to form an ideal crystal structure.
[0054] Comparative Example 3
[0055] The concentration of hydrochloric acid in Example 3 was changed to 3 mol·L -1 , other processes and reaction conditions did not change, and as a result, no two-dimensional lanthanide metal-organic framework crystals were obtained, mainly because the hydrochloric acid concentration was too high, which was not conducive to the coordination of organic ligands.
[0056] Crystal structure analysis:
[0057] The single crystal X-ray diffraction data of Example 3 were recorded at 293 K using a German Bruker Smart Apex II single crystal diffractometer, using a molybdenum target for radiation (λ = 0.71069); the asymmetric unit consists of an Eu 3+ , a deprotonated dptz 2- , a Cl - and two coordinated water molecules. 3+ The coordination environment of Figure 1As shown; each Eu1 forms an eight-coordinate environment, with four oxygen atoms coming from three H 2 dptz ligand, two N atoms from one H 2 dptz ligand, and two oxygen atoms from two water molecules, thus producing a binuclear europium cluster [Eu 2 N 4 (CO 2 ) 4 (H 2 O) 4 ]( Figure 2 ). Further study of the structure showed that the skeleton displayed a two-dimensional network in the ab plane ( Figure 3 and Figure 4 ). In each layer, each H 2 The dptz ligand uses two deprotonated carboxyl groups and two nitrogen atoms to link three [Eu 2 N 4 (CO 2 ) 4 (H 2 O) 4 ]( Figure 5 ), in turn, a binuclear europium cluster connects six H 2 dptz ligand ( Figure 6 ). Therefore, H 2 dptz and binuclear europium clusters can be viewed as 3- and 6-connected points, respectively, thus forming a (3,6)-connected framework ( Figure 7 ).
[0058] Powder X-ray Diffraction (PXRD):
[0059] At 293 K, the test was carried out using a Rigaku model RINT Ultima III diffractometer, and the test angle range was 3-60°; powder X-ray diffraction (PXRD) showed that the simulated and synthesized PXRD spectra of the crystals obtained in Example 3 were well matched at key positions, indicating that they had good crystallinity and phase purity ( Figure 8 ).
[0060] Acid-base stability of crystals in aqueous solution:
[0061] After the crystal sample obtained in Example 3 was dispersed in water for five days, the diffraction peaks of PXRD showed very slight changes, confirming its excellent chemical stability ( Fig. 9 ).like Fig.10As shown, the crystals still have high fluorescence intensity in the pH range of 3-12, and the diffraction peaks of PXRD are consistent with the simulated peaks, indicating that they have excellent fluorescence stability in acid and alkali aqueous solutions. In order to study the thermal stability of the crystals, thermogravimetric analysis was performed at 25-800 °C ( Fig.11 The weight loss around 141°C is about 9.2% (calculated as 10.25%), which is attributed to the removal of free water molecules, and the loss of coordinated water molecules between 141-351°C is 5.1% (calculated as 7.24%). Finally, the framework begins to collapse at 540°C, leaving Eu 2 O 3 Residue (32.56%, calculated as 33.78%).
[0062] Study H 2 Luminescence properties of dptz and crystals at room temperature:
[0063] Under 280 nm excitation, H 2 dptz has a broad emission peak at 460 nm ( Fig.12 ). Due to Eu 3+ of 5 D 0 - 7 F J (J=0-4) transitions, the crystals have transitions at 580 nm, 593 nm, 617 nm, 651 nm and 700 nm (λ ex = 300nm) shows Eu 3+ The typical characteristic emission peak ( Fig.13 ). In addition, in the luminescence spectrum of the crystal synthesized in Example 3, H 2 The emission peak of dptz is almost negligible, which indicates that H 2 dptz can effectively sensitize Eu 3+ .
[0064] Detection of TNP in water:
[0065] Detection of explosives has always been one of the research hotspots, so the potential sensing ability of the crystal synthesized in Example 3 to a series of common nitroaromatic explosives, including 1,3-dinitrobenzene (1,3-DNB), 1,2-dinitrobenzene (1,2-DNB), nitrobenzene (NB), 1,4-dinitrobenzene (1,4-DNB), 2,6-dinitrotoluene (2,6-DNT) and 2,4,6-trinitrophenol (TNP), was tested. In an aqueous solution containing TNP, the fluorescence intensity of the crystal was significantly reduced ( Fig.14 The fluorescence sensing ability of the crystals to TNP was further studied in detail. As the concentration of TNP increased, the fluorescence intensity decreased significantly ( Fig.15), and has a good linear relationship at low concentrations ( Fig.16 ). The fluorescence quenching efficiency can be quantitatively analyzed by the Stern-Volmer (SV) equation:
[0066]
[0067] Among them I 0 and I represent the fluorescence intensity of samples without and with TNPs added, respectively ( 5 D 0 - 7 F 2 ). [A] represents the molar concentration of TNP, Ksv is the quenching constant (M -1 ). The detection concentration limit (LOD) was calculated according to the following formula:
[0068]
[0069] δ is the standard deviation of the detection method. The calculated Ksv value is 0.73×104 M -1 The LOD value was 0.16 μM. In addition, the selectivity of the crystal for TNP in aqueous solution was evaluated by anti-interference experiments. Fig.17 As shown in Figure 2, the crystal can effectively detect TNP even in the presence of other nitroaromatic explosives. At the same time, after five cycles, the fluorescence intensity of the crystal still remains ( Fig.18 ). The above results demonstrate that the crystal can be used as a highly sensitive and recyclable fluorescence sensor to detect TNP.
Claims
1. A two-dimensional lanthanide metal-organic framework material, characterized in that: The two-dimensional lanthanide metal-organic framework material is prepared by an organic ligand H2dptz, and the chemical molecular formula of the organic ligand H2dptz is: 15 H 10 N4O4, the structural formula is as follows: ; The general formula of the two-dimensional lanthanide metal-organic framework material is [Eu(dptz)(H2O)2]Cl·3H2O, which belongs to the monoclinic system, has a space group of P21 / n, unit cell parameters of a(Å)=10.7002(13), b(Å)=14.067(2), c(Å)=12.7584(16), α(°)=90, β(°)=96.207(4), γ(°)=90, and volume V(Å) 3 )=1909.1(4), The molecular formula of dptz is C 15 H8N4O4.
2. A method for preparing the two-dimensional lanthanide metal-organic framework material according to claim 1, characterized in that: The steps include: S1: dissolving europium nitrate hexahydrate and an organic ligand H2dpttz in a mixture of hydrochloric acid, acetonitrile and water to obtain a mixture; the volume ratio of the hydrochloric acid, acetonitrile and water is 1:9.5-10:1.5-2; the concentration of the hydrochloric acid is 0.8-1 mol·L -1 ; S2: The mixture is sealed in a stainless steel autoclave lined with tetrafluoroethylene and heated to 160-170°C at a rate of 10-15°C / h, and then kept warm for 72-78h. After the heating is completed, the mixture is cooled to room temperature, and then repeatedly washed with acetonitrile for 3-5 times to separate and obtain colorless block crystals; S3: Dry the colorless bulk crystals to obtain a two-dimensional lanthanide metal-organic framework material.
3. The method for preparing a two-dimensional lanthanide metal-organic framework material according to claim 2, characterized in that: The mass ratio of the europium nitrate hexahydrate and the organic ligand H2dptz in step S1 is 1.5-2:
1.
4. The method for preparing a two-dimensional lanthanide metal-organic framework material according to claim 2, characterized in that: The amount of hydrochloric acid and the organic ligand used in step S1 is in the following relationship: 45-50 mL: 1 g.
5. The method for preparing a two-dimensional lanthanide metal-organic framework material according to claim 2, characterized in that: The cooling rate in step S2 is 5-8°C / h.
6. The method for preparing a two-dimensional lanthanide metal-organic framework material according to claim 2, characterized in that: The drying in step S3 is performed at room temperature.
7. Use of the two-dimensional lanthanide metal-organic framework material according to claim 1 or the two-dimensional lanthanide metal-organic framework material obtained by the preparation method according to any one of claims 2 to 6 as a fluorescent probe for detecting TNP.
Citation Information
Patent Citations
Dipyridyl triazole rare-earth complex and preparation method thereof
CN103044466A
Bipyridyl triazole rare earth complex and preparation process therefor
WO2014000581A1